Correlation between increased body mass index and reduced lung function in children and adolescents: a systematic (Research, Society and Development, 2022)
Objective: To evaluate studies on the relationship between body mass index (BMI) and lung function in children and adolescents. Methods: Studies were selected with or without a diagnosis of asthma, being compared or associated with lung function and body mass index (BMI) of cross-sectional designs,  cohort, case-control and randomized controlled trials (RCTs). The data were selected using descriptors (("Body Mass Index" OR BMI OR "Body Composition" OR "Body Fat Percentage" OR "Fat Percentage") AND Asthma AND ("Lung function" OR Spirometry)) on the basis of data PUBMED, EMBASE, LILACS, SCIELO. Results: We included 20 articles in the systematic review. Of the total, 10 items 5% found correlations between increasing BMIand changes in lung function (FEV1). Of those found correlations, 5 (50%) reported correlated with the decrease in FEV1 and the remainder with the increase in FEV1. The FVC, 53% has no correlation with the outcome. Regarding the FEV1/FVC ratio 44% found no association. Finally, only 40% correlation between the >IMC with FEF25-75%, and 25% had decreased FEF25- 75% to >BMI. Conclusions: Although most studies have indicated that increased BMI tends to a decrease in lung values, these results and conclusions should  be evaluated with caution.